Thermoneutral conditions in dry reforming of ethanol - Kale, Ganesh R.; Kulkarni, Bhaskar D. (Asia-Pacific Journal of Chemical Engineering, 2014)
The reaction enthalpy (Delta H) of reforming processes like steam and dry (CO2) reforming is of great importance for scale-up and process development. Generally, the reforming processes are considered endothermic in nature. However, a detailed study of the reaction enthalpy of reforming process, taking the example of dry reforming of ethanol considered in this study, reveals the existence of exothermic reaction enthalpy at low temperatures. A study of reaction enthalpy of ethanol dry reforming within pressure (1-10 bar), temperature range (300-900 degrees C), and CO2 to carbon in ethanol ratio (CCER 1-5) was initiated to determine the existence of thermoneutral temperatures for the overall reaction. The variation of thermoneutral conditions and product yields at the thermoneutral temperatures was studied. The utilization potential of the products generated at thermoneutral conditions was also evaluated. The low-pressure thermoneutral operation favored higher hydrogen production, lower methane and water formation, whereas the high-pressure thermoneutral operation favored product gas of lower syngas ratio with higher CO2 conversion (utilization) in the process. The study can be extended to steam and dry reforming of other fuels to generate valuable products at thermoneutral conditions avoiding use of air in the process and subsequent N-2 dilution of the product gas. (c) 2013 Curtin University of Technology and John Wiley & Sons, Ltd.
Keywords: carbon nanofilaments; CO2 utilization; Dry reforming; ethanol to syngas; thermoneutral process